Sources for the breeding of soft spring wheat in the conditions of Novosibirsk region - V. V. Piskarev; E. V. Zuev; A. N. Brykova (Вавиловский журнал генетики и селекции)
The sources were identified among collection samples characterized by highly pronounced economic and valuable features, which allows new geographically remote source material to be taken to the regional breeding practices. This research aims to assess the agronomic traits (duration of the growing period, lodging resistance and plant height, 1000-grain weight, grain weight and yield) in soft spring wheat varieties of different ecological and geographical origin. Estimation was carried out by a 9-point system of expression of the trait during the study, which allows identifying samples with the greatest expression of the trait in the years of study with respect to the average experience. 5439 samples have been studied over 28 years, with 1106 of them, over two years or more. The study was carried out according to the methods of VIR on plots of 2 m2. It was shown that the samples mainly had no correlation between the yield and the duration of the growing period, while the average dependence (г = 0.6) was revealed between the yield and the height of the plants. Varieties forming the intermediate (4.5-5 points) and above average (6-7) yield in a short growing period (69-85 days) were identified (Lutescens 675, Irkut-skaya 49, Simbirca, Hybrid F3 S-141, Hybrid F4, Hybrid F3 S-289 and Hybrid F4 S-2300 and Pamyati Vavenko-va). A high average score (8.6-9) at 1000 grains weight was shown for 16 varieties with variation from 37 g (N43 and IAO-9) to 56 g (Hofed 1). A high average score (8-9) in the evaluation of grain weight was shown for Pamyati Leont'eva, Ekada 70, Simbirtsit, Don Jose, Yong-Liang 4 and Long-Mai 11, which formed ears with an average weight from 0.96 to 2.30 g. A consistently high score (9) reflecting the yield was in the varieties Condestavel, PF 843025, Prilenskaya 19, Pamyati Leont'eva, Omskaya Krasa.